BOOK REVIEW OF DANNY THE CHAMPION OF THE WORLD WRITTEN BY ROALD DAHL - Silvya, Inri Ayu (LANTERN (Journal on English Language, Culture and Literature), 2017)
Danny the Champion of the World is a children novel written by the famous and successful writer of children book, Roald Dahl. Children’s literature is a form of literary work written to be consumed by children containing all the things that are familiar with the world of children. According to O’Sullivan in Historical Dictionary of Children Literature (2010) children’s literature is a literary work which is easily understood by children with casual language and exhilarating story content aimed to build children’s character in the society (O’Sullivan, 2010:5). It can be concluded that children’s literature functions as the medium to provide entertainment containing good stuffs inside to build a good character for children in the society.